MEDICAL PRESCRIPTION FORM AS A TOOL OF COMMUNICATION IN MEDICAL PRACTICE IN MUSCAT: AN EVALUATION STUDY - M. ABUKHADER, MAJED (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The study was conducted to evaluate the quality of the medical prescription form which is used by prescribers who are working in different health care facilities in Muscat, Oman in terms of preprinted contents as well as to study prescribers attitude towards these forms. Methods: for research purposes only, photocopies of 74 blank prescription forms were obtained from 74 health care facilities (71 private and 3 government) and 888 prescriptions were collected, reviewed and analyzed. Results: medical prescription forms collected in the study showed an inconsistency in their preprinted contents as well as an attitude variation amongst prescribers towards the preprinted contents of the prescription forms was recorded. Only 13.51percent of the 74 prescription forms are of an ideal standard quality and 42.45percent of the 888 prescriptions showed prescribers adherence in completely filling in the prescription forms. Conclusion: observations reported in this study regarding the prescription form quality and the prescriber attitude towards these forms could affect the communication between the prescriber and the recipient which ultimately influence patient safety. The policy adopted by the management of the health care facilities in Muscat could be a major contributor to these observations. Key words: Medical prescription form, preprinted contents, prescription errors.